2022
DOI: 10.5944/rppc.29859
|View full text |Cite
|
Sign up to set email alerts
|

Uso de servicios de atención psicológica en jóvenes del sistema de protección y justicia juvenil: Un estudio exploratorio

Abstract: Use of psychological care services in young people from the juvenile justice and protection system: An exploratory study Abstract: The objective was to identify the factors associated (i.e., demographic and clinical) with the use of mental health services in adolescents involved in the juvenile protection and justice system in Catalonia, Spain. The sample consisted of 227 adolescents, aged 12 to 17 years. Apart from gathering sociodemographic and treatment information the Youth Self Report was administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In Spain, no studies have been reported that jointly address the mental health of children and juvenile criminal justice systems. However, a recently published article partially addresses this dimension, focusing on the analysis of psychological care as an entry filter to mental health treatment [81]. The study included a sample of children and adolescents institutionalized in both the protection and juvenile criminal justice systems.…”
Section: Mental Health Care For Juvenile Offendersmentioning
confidence: 99%
“…In Spain, no studies have been reported that jointly address the mental health of children and juvenile criminal justice systems. However, a recently published article partially addresses this dimension, focusing on the analysis of psychological care as an entry filter to mental health treatment [81]. The study included a sample of children and adolescents institutionalized in both the protection and juvenile criminal justice systems.…”
Section: Mental Health Care For Juvenile Offendersmentioning
confidence: 99%